2016
DOI: 10.1016/j.cplett.2016.09.031
|View full text |Cite
|
Sign up to set email alerts
|

A QTAIM exploration of the competition between hydrogen and halogen bonding in halogenated 1-methyluracil: Water systems

Abstract: Using QTAIM we show that the hydrogen bonding complexes of 5-halogenated-1-methyluracil (XmU; X = F, Cl, Br, I or At) with a water molecule were always stronger than the corresponding halogen bonds. The strength of the hydrogen bond decreased with increasing halogen size. The hydrogen bonds displayed an admixture of covalent character but all the halogen bonds were purely electrostatic in nature. An F---O halogen bond was found and was facilitated by an intermediate F---H bonding interaction. The metallicity ξ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…[29,30] By combining interactions that do not compete for the same binding sites, it is, in principle, possible to avoid or at least minimize ''synthon cross-over'', [31] thereby producing architectures of considerable complexity. [34][35][36][37][38][39][40][41][42][43] This is not only because HBs and XBs are similar in strength and properties, but also they are widely applicable to biochemistry and drug design. [33] There are many studies on the competition between various interactions, especially the competition between hydrogen and halogen bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29,30] By combining interactions that do not compete for the same binding sites, it is, in principle, possible to avoid or at least minimize ''synthon cross-over'', [31] thereby producing architectures of considerable complexity. [34][35][36][37][38][39][40][41][42][43] This is not only because HBs and XBs are similar in strength and properties, but also they are widely applicable to biochemistry and drug design. [33] There are many studies on the competition between various interactions, especially the competition between hydrogen and halogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[33] There are many studies on the competition between various interactions, especially the competition between hydrogen and halogen bonds. [34][35][36][37][38][39][40][41][42][43] This is not only because HBs and XBs are similar in strength and properties, but also they are widely applicable to biochemistry and drug design. Alkorta et al studied HBs and XBs formed between hypohalous acid and three nitrogen-containing bases .…”
Section: Introductionmentioning
confidence: 99%
“…Following their footsteps on the path they traced, we here present the experimental charge density analysis of 1-methyluracil (hereinafter 1-MUR), based on a very low-T dataset collected at Caltech in Marsh’s laboratory in 1989 by one of us (RD). Experimental as well as theoretical and computational work on 1-methyluracil and its derivatives have been published a number of times [ 2 , 3 , 4 , 5 , 6 , 7 ], yet the experimental estimates for some of the fundamental properties of the molecule in a condensed phase, such as integrated atomic volumes and charges, as well as atomic and molecular electrostatic quadrupole moments, are not available, to the best of our knowledge, in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The authors investigated the (Y = Br, I, At)/halogenabenzene/NH 3 system [3] and concluded that a halogen bond and a hydrogen bond form with the NH 3 nucleophile. We previously observed for the (X = F, Cl, Br, I, At)/1-methyluracil/H 2 O system that the strength of the hydrogen bond decreased with increasing halogen size, and the hydrogen bonds displayed an admixture of covalent character, but all the halogen bonds were purely electrostatic in nature [5].…”
Section: Introductionmentioning
confidence: 99%